Revisiting, from a Frischian point of view, the relationship between elasticities of intratemporal and intertemporal substitution - Erik Biørn (University of Oslo, Department of Economics, 2017)
How are substitution in the spatial and in the temporal sense connected? Can estimates based on data with spatial variation be transmitted into values appropriate for exploring temporal variation, and vice versa? This paper, building on, inter alia, Frisch (1959), attempts to give some clarifications and provides elements of a synthesis. The income elasticity of the marginal utility of income, whose inverse is often called the 'Frisch parameter', and its multi-period counterpart, the wealth elasticity of the marginal utility of wealth, are key concepts. Three cases with additive preferences are discussed, and in that context the role of the (generalized) 'Frisch parameter' as an overall measure of substitution across commodities and over time is reconsidered.
Keywords: D11; D12; D91; 330; Frisch elasticity; Frisch demand; Intertemporal substitution; Additive preferences; Hometheticity; Marginal utility of income; Marginal utility of wealth